Media coverage of Islam-related news during General Election 13: Analysis of mainstream newspapers - Sedu, Nerawi; A.Manaf, Aini Maznina (2013)
The thirteenth general election saw the two major political parties, BN and PR are dominated by the Malaysian ethnic majority i.e. Malays who are also Muslims. In order to gain public votes, the government use mainstream newspapers to frame Islam-related issues. This research specifically focused on the characterization and information reported about Islam, Muslim and alike during the thirteenth general election. The coverage of these issues by the mainstream newspapers namely Berita Harian, Utusan Malaysia, New Straits Times and The Star was analyzed in this study using content analysis. This analysis aimed to provide a holistic review of the scope of the coverage during the period, but more so, it sought to examine the Malaysian government’ framing of Islam-related issues through the print media in order to gain the Malays’ votes. A total of 178 news articles were analysed using content analysis. It was found that there were 15 dominant issues reported in the newspapers during that period. Among the most frequently reported Islam-related issues were Hudud, Islamic state, kalimah Allah (the word ‘Allah’), sumpah laknat (a retributive oath under syari’ah laws), and apostasy. It was also found that most of the issues were covered the Malay newspapers. In addition, the data also indicated that most of the news were inclined towards supporting the ruling party i.e. Barisan National.